Practices and Approaches of Corporate social responsibility - Jain, Sudha (IJRDO - Journal of Social Science and Humanities Research, 2018)
The definition of CSR used within an organization can vary from the strict "stakeholder impacts" definition used by many CSR advocates and will often include charitable efforts and volunteering. CSR may be based within the human resources, business development or public relations departments of an organisation or may be given a separate unit reporting to the CEO or in some cases directly to the board. Some companies may implement CSR-type values without a clearly defined team or programme. The business case for CSR within a company will likely rest on one or more of these arguments: The term "corporate social responsibility" came in to common use in the early 1970s, after many multinational corporations formed. The term stakeholder, meaning those on whom an organization’s activities have an impact, was used to describe corporate owners beyond shareholders. Proponents argue that corporations make more long term profits by operating with a perspective, while critics argue that CSR distracts from the economic role of businesses. Others argue CSR is merely window-dressing, or an attempt to pre-empt the role of governments as a watchdog over powerful multinational corporations.